2010
DOI: 10.1007/s00259-010-1565-3
|View full text |Cite
|
Sign up to set email alerts
|

Lesion dose in differentiated thyroid carcinoma metastases after rhTSH or thyroid hormone withdrawal: 124I PET/CT dosimetric comparisons

Abstract: We found some suggestions, but no statistically significant evidence, that rhTSH administration results in a lower radiation dose to DTC metastases than does THW. A large, well-controlled, prospective within-patient study should resolve this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 30 publications
2
28
1
1
Order By: Relevance
“…Our actual statement was, "In comparing our data with other reports that evaluated preparation with THW and rhTSH, our data are most consistent with those of Freudenberg et al (6). .…”
Section: Replysupporting
confidence: 88%
“…Our actual statement was, "In comparing our data with other reports that evaluated preparation with THW and rhTSH, our data are most consistent with those of Freudenberg et al (6). .…”
Section: Replysupporting
confidence: 88%
“…Location and size of metastatic lesions can be determined on SPECT/CT imaging, thus guiding management: 131 I therapy is most effective for smaller metastatic deposits [17,18], whereas for large metastases, surgical debulking before 131 I therapy can be considered. While low 131 I activities (1.1 GBq; 30 mCi) successfully ablate normal thyroid tissue remnant located in the thyroidectomy bed [19,20], effective treatment for iodine-avid regional and distant metastatic disease has traditionally required higher 131 I activities, as demonstrated by lesion dosimetry calculation studies [21][22][23][24]. It is important to discuss the study of Castagna et al [25], which assessed the effectiveness of 1.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that there were no differences between rhTSH stimulation and thyroid hormone withdrawal, and therefore that no modifications of prescribed therapeutic activities were necessary. Regarding distant metastases, the same authors [72], retrospectively comparing mean absorbed doses between groups of consecutive patients receiving 124 I PET/CT aided by rhTSH stimulation or thyroid hormone withdrawal, found some indications but no statistically significant evidence that rhTSH administration resulted in a lower radiation dose to DTC metastases than thyroid hormone withdrawal did.…”
Section: Evaluation Of Rhtsh Versus Thyroid Hormone Withdrawal In Raitmentioning
confidence: 98%